2006
DOI: 10.1007/s00221-006-0804-0
|View full text |Cite
|
Sign up to set email alerts
|

Look-ahead fixations: anticipatory eye movements in natural tasks

Abstract: During performance of natural tasks subjects sometimes fixate objects that are manipulated several seconds later. Such early looks are known as "look-ahead fixations" (Pelz and Canosa in Vision Res 41(25-26):3587-3596, 2001). To date, little is known about their function. To investigate the possible role of these fixations, we measured fixation patterns in a model-building task. Subjects assembled models in two sequences where reaching and grasping were interrupted in one sequence by an additional action. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
129
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 153 publications
(150 citation statements)
references
References 47 publications
13
129
0
1
Order By: Relevance
“…Hayhoe and colleagues 19 and Land and colleagues 21 have observed that about one-third of reaching and grasping movements were preceded a few seconds earlier by a fixation on the object. In a similar construction task, Mennie and colleagues 27 reported a 20% rate of look-aheads, a value similar to that found in our study. Thus, patients seem to establish a less efficient planning strategy than controls.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Hayhoe and colleagues 19 and Land and colleagues 21 have observed that about one-third of reaching and grasping movements were preceded a few seconds earlier by a fixation on the object. In a similar construction task, Mennie and colleagues 27 reported a 20% rate of look-aheads, a value similar to that found in our study. Thus, patients seem to establish a less efficient planning strategy than controls.…”
Section: Discussionsupporting
confidence: 91%
“…Look-ahead fixations occur on average 3 seconds before the reach, and their frequency is influenced by task sequence, suggesting that they are purposeful and are thought to reflect planning of the next action. 27 A 2 (group: patients/controls) × 2 (task: familiar/unfamiliar) repeated-measures multivariate ANOVA showed a significant main effect of group (F 1,28 = 6.9, p = 0.013, ηp 2 = 0.20) and task (F 1,28 = 12.1, p = 0.002, ηp 2 = 0.30) on the percentage of lookahead fixations. There was also a significant interaction between group and task (F 1,28 = 4.4, p = 0.044, ηp 2 = 0.14).…”
Section: "Look-ahead" Fixationsmentioning
confidence: 92%
“…An interesting symmetry emerges in these models: Prediction turns motor commands into expected sensory consequences, whereas control turns desired consequences into motor commands. Prediction is readily observed in prehension tasks, where the eyes lead the hand in locating goal targets Mennie, Hayhoe, & Sullivan, 2006). It has been shown in learning studies that prediction emerges faster than control (Flanagan, Vetter, Johansson, & Wolpert, 2003).…”
Section: Computational Modelsmentioning
confidence: 99%
“…When washing one's hands [58] or making a sandwich [59], fixations are occasionally made to objects that are not involved in the current part of the task but will be the focus of an upcoming act. These 'look-ahead' fixations may occur several seconds before that object is used but have a measurable benefit for the efficiency with which the target is later re-acquired [60].…”
Section: Memory During Manipulations In Proximate Spacementioning
confidence: 99%
“…First, and as described here, we may rely more upon remembered information from our allocentric map when constructing the egocentric map. Second, we may vary the reliance upon immediate retinocentric visual information and the egocentric map depending upon the reliability and availability of visual information [60]. Within the visual field itself, the balance between information from vision and memory is likely to vary with eccentricity, with vision dominating in the region around the fovea and being increasingly supplemented by egocentric memory towards the periphery.…”
Section: (C) Spatial Memory In Natural Tasksmentioning
confidence: 99%